Radiation physics for nuclear medicine - Cantone, M. C.; Hoeschen, Christoph; SpringerLink (Online service). (Berlin London Springer, 2010)
The field of nuclear medicine is expanding rapidly, with the development of exciting new diagnostic methods and treatments relevant to a variety of diseases. This growth is closely associated with significant advances in radiation physics. In this book, acknowledged experts explain the basic principles of radiation physics in relation to nuclear medicine and examine important novel approaches in the field. The first section is devoted to what might be termed the "building blocks" of nuclear medicine, including the mechanisms of interaction between radiation and matter and Monte Carlo codes. In subsequent sections, radiation sources for medical applications, radiopharmaceutical development and production, and radiation detectors are discussed in detail. New frontiers are then explored, including the PET magnifying probe, improved algorithms for image reconstruction, biokinetic models, and voxel phantoms for internal dosimetry. Both trainees and experienced practitioners and researchers will find this book to be an invaluable source of up-to-date information.
Part I Introduction -- The Role of Radiation Physics in Nuclear Medicine -- The Molecular Imaging Pathway to Biomedical Physics -- Part II Fundamental Processes on Radiation Physics -- Mechanisms of the Interactions Between Radiation and Matter -- Principles of Monte Carlo Calculations and Codes -- Part III Radiation Sources and Radiopharmaceutical Productions -- Sealed Radionuclide and X-Ray Sources in Nuclear Medicine -- Radiopharmaceutical Production -- Research and Development of New Radiopharmaceuticals -- Part IV Radiation Detectors for Medical Applications -- Basic Principles of Detection of Ionizing Radiation Used in Medical Imaging -- Scintillators and Semiconductor Detectors -- New Trends in Detectors forMedical Imaging -- Part V New Frontiers in Nuclear Medicine -- The PET Magnifier Probe -- Algorithms for Image Reconstruction -- Biokinetic Models for Radiopharmaceuticals -- Voxel Phantoms for Internal Dosimetry.
Electronic reproduction.
Keywords: Nuclear medicine; Medical physics; Electronic books